A Queer Critique of Looking for "Male" and "Female" Voices in the Hebrew Bible - Tamber-Rosenau, Caryn (The Oxford handbook of feminist approaches to the Hebrew Bible, 2020)
The idea that biblical scholars discern the “gender” of a text or tradition by examining a text’s worldview, voice, and use of language gained currency in the 1990s with Athalya Brenner and Fokkelien van Dijk-Hemmes’s On Gendering Texts: Female and Male Voices in the Hebrew Bible. Since then, a steady stream of books and papers has made the case for “masculine” or “feminine” voices in various biblical narratives. Although the boom in scholarship searching for “M” or “F” voices in biblical texts coincided with the growth of queer-theoretical and gender-critical approaches to the Bible, no queer-influenced critique of the practice of gendering texts has yet emerged. This essay argues that the M/F textual schema both implies and reinforces a fixed gender binary, a notion rejected by queer theory in general and queer biblical criticism in particular. In other words, the attempt to recover female voices in the Hebrew Bible is a noble goal, but the conviction that an exegete provides such a recovery by looking to a text’s stereotyped “gendered” language or interests is unhelpful to feminist biblical studies.